Trainers : Or the Brutal Unpleasant Atmosphere of this Most Disagreeable Season: a Theatrical Essay. - Oswald, Sylvan (Oberon modern plays., 2020)
The only rule is to break the rules. In a parallel present, two queer radicals meet in the fallout of The Second American Civil War. If love is the most radical act, can their desire survive the revolution? Based on Montaigne's intellectual love affair with political thinker Étienne de La Boétie, Sylvan Oswald's brand-new play Trainers is a visionary story exploring the different ways we can connect as lovers, activists, and humans.